Impact of Sharia Compliance and Islamic Corporate Governance on Financial Performance of Islamic Banks Moderated by Islamic Corporate Social Responsibility - Baso Pangerang; Ledy Setiawati; Anisa Abubakar Lahjie (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to analyse the effect of Islamic Corporate Social Responsibility (ICSR) moderated by Sharia Compliance and Islamic Corporate Governance (ICG) on the Financial Performance of Islamic Commercial Banking in Indonesia. This study uses secondary data from 9 (nine) Banks in the period of 2017 - 2022 by using purposive sampling technique and Multiple Regression Analysis. The results showed that Sharia Compliance and ICG have a significant and positive effect on financial performance. Furthermore, the results related to moderation variables show that ICSR moderates the effect of Sharia Compliance on Financial Performance, research also shows that ICSR moderates the effect of ICG on Financial Performance. The implications of this research are as follows: (i) increasing the Profit Sharing Ratio as a form of sharia compliance (ii) implementing ICG principles with monitoring and supervising by the Sharia Supervisory Board and conducting regular evaluations through self-assessment. (iii) more sustainable ICSR practices among Islamic banking that are in line with Islamic values.